The mechanism of Guanxin Qiwei dropping pills target Dubosiella to improve atherosclerosis - Liao, Yuanhong; Li, Jun; Li, Yuxin; Liu, Jing; Chen, Tingting; Lu, Jingkun; Li, Hongxia; Zhang, Qian; Wang, Yuewu (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the therapeutic effects of Guanxin Qiwei dropping pills (GXQW) on atherosclerosis (AS) and to delineate the mechanisms underlying these effects.MethodsFirst, the chemical constituents of GXQW were identified using liquid chromatography-mass spectrometry (LC-MS). In addition, 15 batches of GXQW were used for fingerprint determination. Subsequently, an ApoE−/− mouse model of AS induced by a high-fat diet was established. Lipid deposition, plaque coverage, and collagen fiber content in the aortic arch were evaluated using Oil Red O, H&E, and Masson’s trichrome staining, respectively. Enzyme-linked immunosorbent assay (ELISA) kits were employed to quantify serum oxidative stress markers, inflammatory cytokines, and lipid profiles. Additionally, fecal samples were subjected to 16S rRNA sequencing to investigate the effects of GXQW on intestinal dysbacteriosis. Differential gut microbiota were identified at the phylum-to-genus level. Furthermore, untargeted serum metabolomics was conducted to explore the potential metabolic pathways through which GXQW ameliorated AS.ResultsA total of 118 chemical constituents were identified in GXQW through database comparison. Compared to the model group, GXQW treatment attenuated lipid deposition and plaque coverage in the aortic arch and mitigated collagen depletion. Fingerprint analysis showed the consistency and stability of the quality of GXQW. Additionally, GXQW reduced total cholesterol (TC) and triglyceride (TG) levels, decreased the concentrations of inflammatory cytokines interleukin-6 (IL-6) and interleukin-1beta (IL-1β), suppressed malondialdehyde (MDA) activity, and elevated superoxide dismutase (SOD) levels. In terms of gut microbiota modulation, high-dose GXQW treatment promoted the abundance of Bacteroidota and decreased Firmicutes, particularly the Dubosiella genus within Firmicutes. KEGG pathway enrichment analysis of serum metabolites revealed that pathways associated with lipid metabolism, including Glycerophospholipid metabolism, Citric acid cycle (TCA cycle), and Arachidonic acid metabolism, were notably enriched. P-cresol sulfate (PCS) and other metabolites were identified as the potential metabolic biomarkers underlying the therapeutic effects of GXQW on AS. The correlation analysis further demonstrated a significant positive correlation between Dubosiella and the aforementioned metabolites.ConclusionThe findings suggest that GXQW exerts evident therapeutic effects on AS by regulating gut microbiota and serum metabolic biomarkers.